Removal of Zinc and Ferum using Tilapia Fish Scale - Zayadi, Nabilah; Othman, Norzila (International Journal of Integrated Engineering, 2013)
Abstract: Wastewater contains large amount of contaminants, especially heavy metals, organic toxicants, and human pathogens. Heavy metal contamination had become major problem in water pollution. The use of current treatment causes some drawback even though major pollutant in wastewater already removed. Removal of zinc and ferum from synthetic wastewater using Tilapia fish scale as biosorbent was studied. This study was focused on batch method by varying pH, biosorbent dosage, contact time and initial metal ion concentration. Adsorption characteristic of fish scale before and after treatment were analysed by Scanning Electron Microscopy (SEM), X-Ray Fluorescence (XRF), and Fourier Transform Infrared (FTIR) while concentration of zinc and ferum was obtained by Inductively Coupled Plasma-Mass Spectrometer (ICP-MS) and Atomic Adsorption Spectroscopy (AAS) respectively. The maximum percentage removal was found at 93.52% of zinc and 65.9% of ferum under best optimum adsorption conditions: pH = 6, 4.5, biosorbent dosage = 0.02 g/100 mL, 0.8 g/100 mL, concentration = 10 ppb, 300 ppb and 3 hours contact time for ferum and zinc. The finding indicated that promising biosorption of zinc and ferum using Tilapia fish scale as biosorbent.